Pengaruh Sistem Pengendalian Internal, Kemampuan Sumber Daya Manusia, Pemanfaatan Teknologi Informasi dan Komitmen Organisasi terhadap Kualitas Pelaporan Barang Milik Negara - Zulpahmi Zulpahmi; Sumardi Sumardi; Shandy Kurnia Yasinanda (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study aims to determine how much influence the internal control system, human resource capabilities, use of information technology and organizational commitment have on the quality of reporting on state property. The sample in this study was 100 employees of Lapas Kelas I Cipinang. Regression analysis reveals that the quality of reporting of state property is partly not affected by the internal control system. The quality of reporting on state property is partly not affected by the ability of human resources. The quality of state property reporting is partially unaffected by the use of information technology. The quality of state property reporting is partly influenced by organizational commitment. The quality of reporting on state property is influenced by the internal control system, human resource capabilities, the use of information technology, and organizational commitment simultaneously.